Development Modern Physics Digital Handout Based on Technology Literacy - Salmah Rianti; Hamdi Akhsan; Ismet Ismet (Berkala Ilmiah Pendidikan Fisika, 2020)
This study aims to produce a valid and practical modern physics digital handout based on technology literacy through the adaptation of Rowntree product development model procedures and Tessmer formative evaluation on the physics education study program, FKIP, Sriwijaya University. The data was collected by walkthrough and questionnaire technique. The result showed the mean score for the validity of the digital handout was 4,53 for design, content, and linguistic aspects with a highly valid category. The practicality average score in the one-to-one evaluation stage and the small group evaluation stage were 79,08% and 84,59% respectively, both of them with a practical category. Thus, the developed modern physics digital handout based on technology literacy was very valid and practical.